The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/aswp.12270
|View full text |Cite
|
Sign up to set email alerts
|

Social behavior practices for child protection and well‐being among low‐income urban households in Bangladesh

Abstract: The main objective of this study was to explore the status of social behavior practices for child protection and well‐being among low‐income urban households in Bangladesh. This study used a survey method, and data were collected through a face‐to‐face structured interview from 378 low‐income household heads from 12 wards (Konabari and Kashimpur) of Zone 5 of the Gazipur City Corporation. Results found that the current status of the presence of child protection services is very low (in many cases, this number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In addition, the UAE launched a Family Protection Policy, which seeks to strengthen social ties in UAE families and communities ( 71 ). It is also important to develop innovative child/adolescent-friendly initiatives and secure their participation by including their views when considering overall protection and their best interests ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the UAE launched a Family Protection Policy, which seeks to strengthen social ties in UAE families and communities ( 71 ). It is also important to develop innovative child/adolescent-friendly initiatives and secure their participation by including their views when considering overall protection and their best interests ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Good health is central to handling stress and living a longer, more active life. On the other hand, the concept of ‘well-being’ is complicated and multifaceted (Islam et al, 2023). It is the ‘state of being comfortable, healthy, or happy’ (Reza et al, 2019).…”
Section: Disparities In Asian Arab Countriesmentioning
confidence: 99%
“…health awareness among mothers, hand washing practice before and after meal and after defection, avoiding early child marriage, etc.) are important for child protection and well‐being among low‐income families (Islam et al, 2023). It is also found that children's well‐being may be influenced by children's own resilience, parent–child attachment, and parental marital relationship.…”
mentioning
confidence: 99%